Poverty Representation and Social Issues in Jesmyn Ward’s Sing, Unburied, Sing - Raihan Syach Bustami Harahap; Nurholis; Badri Khaeruman (Universitas Insan Budi Utomo, 2024)
Literature provides a unique perspective on the social issues of the time in which it was written. This research will explore the representation of poverty and social issues in a novel using the theoretical framework provided by literary analysis and social context. Poverty and social issues in the novel Sing, Unburied, Sing, by Jesmyn Ward will be one of the variables with a large role. The novel explores aspects of race, family, and social issues that emphasise the effects of poverty on the characters. This research was conducted using a descriptive qualitative research approach with a text analysis design. The subject of this research is poverty and social issues. Meanwhile, the data or object of research is Jesmyn Ward’s nove entitled Sing, Unburied, Sing. The technique for collecting data is observation and noting technique. Based on the findings, the author concludes that there are at least several representations of poverty and social issues depicted through the narrative and dialogue in this novel. Some of these issues are represented by the depiction of Jojo's home environment, situated in a remote forest area, with a lack of basic hygiene standards.